Ump researchers' sterling performance in British Invention Show 2015 - Hazlina, Faizal (Penerbit UMP, 2015)
Three researchers from Universiti Malayia Pahang (UMP) made name for themselves at the international arena when they won numerous special awards and gold medals in the British Invention Show (BIS) 2015 which was held at the Barbican Exhibition Centre, London.